Tactical Urbanism Along the PNR Railways of Manila as a Catalyst for Transit Oriented Development in a Dense Metro - Esquivel, Regine Marie C.
The Philippine National Railway (PNR) is a national transportation legacy with rich value that deserves high regard when it comes to optimum utilization (Licerio, 2008). Bettering the railways does not only mean the stations’ façade and structure but also its long extent of railways that stretches from Northern to Central Luzon traversing different land uses. With the idea of bettering the transportation, its adjacent lots and open spaces are being used by the communities to serve as a place of informal use. Community facilitated spaces are then made by the neighborhood to cater to their recreation and visual needs through tactical urbanism. To treat contemporary urban paradigms, Tactical Urbanism aims to recover and activate spaces through fast and easily applied actions that allow the possibility of large-scale and long-term changes in the city (Barata & Fontes, 2017). The purpose of this study is to highlight the potential of Tactical Urbanism in promoting Transit Oriented Development by revealing opportunities for a compact, walkable, pedestrian-oriented, mixed used communities centered around the train system. For that, the researcher conducted mapping, surveys, and interviews to gather data, define and characterize different typologies along the site, measure community perception on the tactical urbanism created by the neighborhoods to cater to their activities, and assess these tactics through the lens of landscape architecture. The study implies that there are several basic preferences of open spaces and neighborhood facilities that cater to an urban community and that tactical urbanism is affected by the demand of their purpose and land use of its placement. The research study dwells on the use of spaces adjacent to the PNR rails of Manila as a way of neighborhoods to maximize and improve the social environment for its users.